Numerical Prediction of Flow Induced Fibers Orientation in Injection Molded Polymer Composites - A. N., Oumer; N. M., Hamidi; Idris, Mat Sahat (2015)
Since the filling stage of injection molding process has important effect on the determination of the orientation state of the fibers, accurate analysis of the flow field for the mold filling stage becomes a necessity. The aim of the paper is to characterize the flow induced orientation state of short fibers in injection molding cavities. A dog-bone shaped model is considered for the simulation and experiment. The numerical model for determination of the fibers orientation during mold-filling stage of injection molding process was solved using Computational Fluid Dynamics (CFD) software called MoldFlow. Both the simulation and experimental results showed that two different regions (or three layers of orientation structures) across the thickness of the specimen could be found: a shell region which is near to the mold cavity wall, and a core region at the middle of the cross section. The simulation results support the experimental observations that for thin plates the probability of fiber alignment to the flow direction near the mold cavity walls is high but low at the core region. It is apparent that the results of this study could assist in decisions regarding short fiber reinforced polymer composites.